Final report : comprehensive institutional review of the Caribbean Meteorological Organisation (CARICAD MaracasTT, 2004)
Provides a review of the organization, management and operations of the various organs of the Caribbean Meterological Organization.
Keywords: METEOROLOGICAL SERVICES